Some aspects of regulating financial activity of state aviation enterprises - Садловська, І. П. (Proceedings of National Aviation University (archive), 1999)
Considered are some problems of regulating financial activity of aviation enterprises. Determined are prerequisites to the analysis of liquidity and capacity to pay, also given are the values of the maim indeces